Project Based Learning in Elementary Descriptive Writing: Pembelajaran Berbasis Proyek dalam Penulisan Deskriptif di Sekolah Dasar - Indahyati, Silvia; ZULIKHATIN NUROH, ERMAWATI (Indonesian Journal of Education Methods Development, 2025)
General background: Writing skills are essential competencies in elementary education, yet many students struggle to express ideas clearly through descriptive texts. Specific background: Conventional approaches in Indonesian language classes often limit students’ creativity and engagement. Knowledge gap: Few studies have explored the structured implementation of Project Based Learning (PjBL) for descriptive writing at the elementary level. Aims: This study aimed to analyze the implementation of PjBL in teaching descriptive text writing to fourth-grade students at SDN Sukorejo 4, Pasuruan. Results: Using a qualitative case study design, data were collected through observation, interviews, and documentation with teachers and students. The PjBL model was implemented through six structured phases: identifying phenomena, formulating core questions, designing project plans, arranging project schedules, monitoring progress, testing outcomes, and conducting evaluations. All phases were successfully executed and supported student engagement in descriptive writing. Novelty: The study highlights how PjBL fosters creativity, critical thinking, and collaborative learning in elementary language education. Implications: Findings suggest that structured PjBL strategies can serve as an effective alternative to traditional methods, offering meaningful learning experiences and supporting writing skill development in early education. Highlights: PjBL structured in six phases improved descriptive writing. Study provides a novel application at elementary level. PjBL supports creativity, engagement, and collaborative learning. Keywords: Project Based Learning, Descriptive Writing, Elementary Education, Creativity, Qualitative Study